Osobennosti postroenija processa trenirovki junych borcov greko-rimskoo stilja - Dachnovskij, V. S.; Korzenevskij, A. N.; Podlivaev, B. A.; Portugalov, M. N.; Trifonov, V. N. (Fiziceskaja Kultura: vospitanie, obrazovanie, trenirovka, 2006)
Till now the attempts of complex studying of the changes in the physical efficiency (PE) and power endurance (PwE), in the adaptation of cardiac system, neuro-muscular apparatus and central nervous system to the loadings at different stages of training were not undertaken. There are no data on interrelation of the parameters of PE with the result of young athletes of elite categories, and also about the influence of the intense PwE on the changes of separate sides of the wrestlers' preparedness.